J.-M. G. Le Clézio: ressonâncias surrealistas - Silva Camarani, Ana Luiza [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
A partir de três obras de Le Clézio – o romance Voyages de l’autre cote (1975), o ensaio L’Inconnu sur la terre (1978) e o conto “Lullaby”, este integrando o livro de contos intitulado Mondo et autres histoires (1978) –, pretende-se focalizar os diálogos que esses textos estabelecem com a literatura surrealista ao fazer emergir o real oculto e determinar uma realidade ampliada.

Concentrating on three works by Le Clezio - the novel "Voyages de l'autre cote" (1975), the essay "L'Inconnu sur la terre" (1978) and the short story "Lullaby", this last one included in the short story collection titled "Mondo et autres histories" (1978) -, this paper aims at focusing on the dialogs these texts establish with the surrealist literature when they make the hidden real emerge and determine an expanded reality.
J.-M. G. Le Clezio: surrealist resonances
Keywords: French literature; Narrative; Poetry; Intertextuality